An extension of adaptation algorithms for 2-D feedforward neural networks - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
The generalized weight adaptation algorithms presented in (Kuschewski et al., 1993; Zak and Sira-Ramirez, 1990) are extended for 2-D madaline and 2-D two-layer FNN's.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka